Strategic Integration of ESG Principles: An Analysis of Sustainable Business Practice at NWP Property - Adrian Pratama; Jerry Heikal (Sean Institute, 2024)
Currently, environmental, social, and governance (ESG) principles have become guideline for companies in the pursuit of sustainable business practices, taking into consideration their impact on the environment, society, and the implementation of good corporate governance. ESG principles are then integrated into a company's business activities and are no longer merely an option in their implementation. The objective of this research is to analyse the strategies for integrating ESG principles into the business practices of commercial real estate companies. This study was employed a qualitative methodology to understand and comprehend the conditions of a company as the research subject. The research sample consists of the Head of Research and ESG, Supervisor of the Energy and Sustainability team, and Head of Operations across all malls owned by NWP Property. The Grounded Theory approach is utilized in this research to derive research answers from data collected through interviews with the respondents, followed by a transcription stage to identify codes, categories, and themes. Based on the research findings, three themes are identified to address the research question. First,